2022
DOI: 10.1007/s10826-022-02298-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the SPARK Teen Mentoring Program for High School Students

Abstract: This study employed a randomized controlled trial with pre- and post-intervention measurement to investigate the impact of the Speaking to the Potential, Ability, and Resilience Inside Every Kid (SPARK) Teen Mentoring program on knowledge of the principles of mind, thought, and consciousness; communication, decision making, and problem-solving skills; emotional regulation; and resilience. The SPARK program is a resilience-focused social-emotional learning program designed to promote youth resilience, emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recently, Green et al, (2022) studied the effectiveness of the SPARK program with adolescents and reported their experiences during a resilience based SEL program. Their findings highlighted the potential effectiveness of the SPARK Teen mentoring program in that it increased youth's awareness and management of their emotions, as well as their understanding of the connection between their thoughts and their emotions.…”
Section: ) Strengths Limitations and Implicationsmentioning
confidence: 99%
“…Recently, Green et al, (2022) studied the effectiveness of the SPARK program with adolescents and reported their experiences during a resilience based SEL program. Their findings highlighted the potential effectiveness of the SPARK Teen mentoring program in that it increased youth's awareness and management of their emotions, as well as their understanding of the connection between their thoughts and their emotions.…”
Section: ) Strengths Limitations and Implicationsmentioning
confidence: 99%